SERVICE QUALITY AND CUSTOMER SATISFACTION THROUGH AIRQUAL DIMENSIONS: AN EMPIRICAL INVESTIGATION ON IRAQI AIRWAYS - Alaa S. Jameel (International Journal of Management Studies)
In today’s rapidly evolving business environment, customer requirements and expectations are continually increasing. Many service-oriented companies, including airlines, are struggling to accurately understand and meet the true needs and desires of their passengers. Often, they rely on outdated views of airline services. This study investigated how various dimensions of service quality impact customer satisfaction at Iraqi Airways. Using a convenience sampling technique, data were collected through questionnaires distributed at Baghdad International Airport and Erbil International Airport in Iraq. A total of 381 valid responses were analyzed using Structural Equation Modelling (SEM). The results indicate that five service quality dimensions—airline tangibles, terminal tangibles, security and safety, personnel services, and airline image—have a positive and significant effect on customer satisfaction. However, empathy does not significantly influence customer satisfaction. The findings suggest that Iraqi Airways should focus on differentiating its services to enhance customer satisfaction. Managers are encouraged to concentrate on factors that elevate service quality, thereby improving customer satisfaction. This study can assist Baghdad International Airport and Erbil International Airport in understanding the importance of service quality, which could lead to higher passenger satisfaction and foster long-term relationships with their customers.